THE EFFECT OF COMPOUND EXERCISES ON DEVELOPING A NUMBER OF FUNCTIONAL VARIABLES FOR YOUNG FOOTBALL PLAYERS - Assist Lecturer Zeyad Ahmed Diab (Galaxy International Interdisciplinary Research Journal, 2023)
The research aims to preparing Compound exercise in developing some functional variants for the young footballers. Recognizing the effect of the exercise for developing Some of functional changes. The Society of the research represents the players who participating in the Champion of Salah AL Din under20 years old players. while the Sample of the research represents the footballers of Salah AL-Din club under 20 years old players and the data were processed by using the ready-made program Statistical Scheme spss. The Conclusions, The Compound exercise had positive effects while the experimental research sample level in the functional changes. The Recommendations, Using the proposed exercise in developing the young footballers.